Two novel CreERT2 transgenic mouse lines to study melanocytic cells in vivo - Stüfchen, Isabel; Beckervordersandforth, Ruth; Fischer, Stefan; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Beyer, Felix (Pigment Cell & Melanoma Research, 2022)
The skin of adult mammals protects from radiation, physical and chemical insults. While melanocytes and melanocyte-producing stem cells contribute to proper skin function in healthy organisms, dysfunction of these cells can lead to the generation of malignant melanoma—the deadliest type of skin cancer. Addressing cells of the melanocyte lineage in vivo represents a prerequisite for the understanding of melanoma on cellular level and the development of preventive and treatment strategies. Here, the inducible Cre-loxP-system has emerged as a promising tool to specifically target, monitor, and modulate cells in adult mice. Re-analysis of existing sequencing data sets of melanocytic cells revealed that genes with a known function in neural cells, including neural stem cells (Aldh1L1 and Nestin), are also expressed in melanocytic cells. Therefore, in this study, we explored whether the promoter activity of Nestin and Aldh1L1 can serve to target cells of the melanocyte lineage using the inducible CreERT2-loxP-system. Using an immunohistochemical approach and different time points of analysis, we were able to map the melanocytic fate of recombined stem cells in the adult hair follicle of Nestin-CreERT2 and Aldh1L1-CreERT2 transgenic mice. Thus, we here present two new mouse models and propose their use to study and putatively modulate adult melanocytic cells in vivo.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Aldh1L1-CreER; inducible Cre mouse line; melanocyte; melanocyte stem cell; multipotent stem cell; Nestin-CreER